Analisa Tradisi Pernikahan Siji Jejer Telu Ditinjau dari Fiqih Munakahat dan ‘Urf - Awalia, Fadhila Tianti Mudi; Syarifah, Eka Sayidatu; Hidayati, Noor Kholifah; Sarjana, Sunan Autad; Elita, Yana (STAI Nurul Islam Mojokerto, 2025)
This study aims to examine the view of fiqh of marriage (fiqh munakahat) and the principle of ‘urf regarding the prohibition of the siji jejer telu marriage, as well as to understand the community's perspective on this prohibition in Desa Carangrejo, Kecamatan Sampung, Kabupaten Ponorogo. The research method used is qualitative descriptive. The data collected by the researcher comes from interviews, observations, and documentation. The results of the study show that most of the people in Desa Carangrejo, Kecamatan Sampung, Kabupaten Ponorogo still believe in the prohibition of the siji jejer telu marriage with the aim of avoiding several negative consequences that are believed to occur if the prohibition is violated. This belief is based on the source from one of the community leaders, Mr. Sukar. In fiqh munakahat, there is no prohibition on marriage based on birth order, such as the siji jejer telu marriage. Islam stipulates that if the essential elements and conditions of marriage are fulfilled, the marriage is considered valid. However, if any of the conditions are missing, the marriage is considered invalid because it does not meet the necessary requirements. The siji jejer telu marriage tradition falls into the category of incorrect customs or ‘urf fasid, as this belief contradicts and is inconsistent with Islamic law (syariat).